Quantitation of the ataxia‐telangiectasia‐mutated and Rad3‐related inhibitor elimusertib (BAY‐1895344) in human plasma using LC–MS/MS. (8th August 2022) - Kiesel, Brian F.; Parise, Robert A.; Krishnamurthy, Anuradha; Gore, Steven; Beumer, Jan H.
Abstract: Ataxia‐telangiectasia‐mutated and Rad3‐related (ATR) is master regulator of the DNA‐damage response that, through multiple mechanisms, can promote cancer cell survival in response to replication stress from sources, including chemotherapy and radiation. Elimusertib (BAY‐1895344) is an orally available small‐molecule ATR inhibitor currently in preclinical and clinical development for cancer treatment. To support these studies and define elimusertib pharmacokinetics, we developed a HPLC–MS method for its quantitation. A 50‐μL volume of plasma was subjected to acetonitrile protein precipitation and then chromatographic separation using a Phenomenex Polar‐RP column (2 × 50 mm, 4 μm) and a gradient mobile phase consisting of 0.1% formic acid in acetonitrile and water during a 7‐min run time. Mass spectrometric detection was achieved using a SCIEX 4000 triple‐stage mass spectrometer with electrospray positive‐mode ionization. With a stable isotopic internal standard, the assay was linear from 30 to 5000 ng/mL and proved to be both accurate (93.5–108.2%) and precise (<6.3% coefficient of variation) fulfilling criteria from the Food and Drug Administration guidance on bioanalytical method validation. This LC–MS/MS assay will support several ongoing clinical studies by defining elimusertib pharmacokinetics.